Formation of helical dislocations in ammonothermal GaN substrate by heat treatment. (18th January 2016) - Horibuchi, Kayo; Yamaguchi, Satoshi; Kimoto, Yasuji; Nishikawa, Koichi; Kachi, Tetsu
Abstract: GaN substrate produced by the basic ammonothermal method and an epitaxial layer on the substrate was evaluated using synchrotron radiation x-ray topography and transmission electron microscopy. We revealed that the threading dislocations present in the GaN substrate are deformed into helical dislocations and the generation of the voids by heat treatment in the substrate for the first observation in the GaN crystal. These phenomena are formed by the interactions between the dislocations and vacancies. The helical dislocation was formed in the substrate region, and not in the epitaxial layer region. Furthermore, the evaluation of the influence of the dislocations on the leakage current of Schottky barrier diodes fabricated on the epitaxial layer is discussed. The dislocations did not affect the leakage current characteristics of the epitaxial layer. Our results suggest that the deformation of dislocations in the GaN substrate does not adversely affect the epitaxial layer.